2018
DOI: 10.7717/peerj.5574
|View full text |Cite
|
Sign up to set email alerts
|

Profiling exercise intensity during the exergame Hollywood Workout on XBOX 360 Kinect®

Abstract: BackgroundDespite the increasing popularity of exergame practice and its promising benefits in counteracting physical inactivity, limited research has been performed to document the physiological responses during an exergame session. This study aims (i) to investigate the responses of heart rate (HR) and oxygen uptake () during an exergame session and to compare with HR and measured during joystick session and (ii) to compare HR and obtained during exergame and joystick session with those HR and associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 32 publications
3
30
0
Order By: Relevance
“…31,32 Exergames comprise many different modalities (walking, running, climbing stairs, cycling, rowing, swimming, baseball, ping-pong, tennis, balance training, frisbee, boxing, canoeing, stretching exercises, bowling, golf, resistance exercises, yoga, dancing, etc.) [21][22][23]26,30 and are based on the idea of integrating physical activity and exercise with appealing digital games. 33 We believe that some modalities may be better than others at reducing anxiety levels, especially those classified as being of moderate intensity.…”
Section: Exergames and Anxiety Disorders During Covid-19 Quarantine: mentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Exergames comprise many different modalities (walking, running, climbing stairs, cycling, rowing, swimming, baseball, ping-pong, tennis, balance training, frisbee, boxing, canoeing, stretching exercises, bowling, golf, resistance exercises, yoga, dancing, etc.) [21][22][23]26,30 and are based on the idea of integrating physical activity and exercise with appealing digital games. 33 We believe that some modalities may be better than others at reducing anxiety levels, especially those classified as being of moderate intensity.…”
Section: Exergames and Anxiety Disorders During Covid-19 Quarantine: mentioning
confidence: 99%
“…16 These characteristics are crucial for increasing motivation and self-efficacy, as well as for possibly keeping people physically active. 17 Previous studies have shown that exergame interventions are able to improve the following: physical activity levels, 18 the performance of daily activities, 19,20 heart rate, [21][22][23][24][25] oxygen consumption, 21,23,25 and energy expenditure in various populations 21,23,25,26 ; improvements in body composition in children 27 ; and postural balance 28 and cognitive function in older adults. 29 Moreover, it has already been demonstrated that a single session of a dance exergame reduced anxiety levels in young adult women.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, data demonstrating moderate-to-vigorous intensities in exergaming have been limited either by relying on HR to assess exercise intensity and/or by simulating traditional exercise. [18][19][20] What are the new findings ► Oxygen uptake whilst playing a biking exergame can be classified as moderate to vigorous. ► Exercise intensity during exergaming was unaffected by aerobic fitness.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, this exergame has several pre-established training protocols that consist of standardized exercises. Due to the feasibility of performing the exercises while coupling the participant to the metabolic system, the training protocol used in the present study was Sports Athlete [10]. For additional details about this protocol, see Viana et al [10] and ▶table 1.…”
Section: Exergame Sessionmentioning
confidence: 99%
“…Exergame participation may increase heart rate (HR), oxygen uptake (VO 2 ), and energy expenditure (EE) [5][6][7][8][9][10][11] and for these reasons, could positively impact daily energy balance and promote significant weight loss [12]. Indeed, knowledge about EE might be important for practitioners and health professionals, since it can help to adapt diets and obtain insights into possible outcomes (i. e., weight management).…”
Section: Introductionmentioning
confidence: 99%